The Combined Role of Independence in Self-Concept and A Collectivistic Value Orientation in Group-Focused Enmity in Korea - Lee, Hayeon (International journal of conflict and violence, 2022)
Previous research (Zick et al. 2008) suggested that animosity toward social minorities in Europe is intertwined, forming a syndrome of Group-Focused Enmity (GFE). In the current research, we extended the notion of GFE by identifying the GFE structure in a non-European context (South Korea). We also tested a novel hypothesis that stipulates an interplay between individuals’ self-concept and their value orientation in predicting the overall level of GFE. Two nation-wide surveys in South Korea showed that antagonism toward social minorities that have typically been marginalized and devalued in that country forms GFE while reflecting the unique intergroup context of Korean society. Further, we found as expected that independence in self-concept and a collectivistic value orientation jointly predict lower levels of GFE (Study 1). When political orientation and national identification were taken into account, the predicted interaction was observed only on antagonism toward ingroup minorities but not toward outgroup minorities by race or ethnicity (Study 2). Implications of these findings and directions for research on GFE are discussed.